2020
DOI: 10.1016/j.heliyon.2020.e04027
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic interaction of a consortium of the brown-rot fungus Fomitopsis pinicola and the bacterium Ralstonia pickettii for DDT biodegradation

Abstract: Trichloro-2,2-bis (4-chlorophenyl) ethane (DDT) is a toxic and recalcitrant pesticide that has been greatly used to eradicate malaria mosquitos since the 1940s. However, the US Environmental Protection Agency banned and classified DDT as priority pollutants due to its negative impact on wildlife and human health. Considering its negative effects, it is necessary to develop effective methods of DDT degradation. A synergistic interaction of a consortium consisting of the brown-rot fungus Fomitopsis pinicola and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 77 publications
0
22
0
Order By: Relevance
“…A common approach is to use both fungi and bacteria to enhance degradation since fungi can transform pesticides into an easier and accessible form for bacteria [79].…”
Section: Fungal Degradationmentioning
confidence: 99%
“…A common approach is to use both fungi and bacteria to enhance degradation since fungi can transform pesticides into an easier and accessible form for bacteria [79].…”
Section: Fungal Degradationmentioning
confidence: 99%
“…Mycoremediation is one of the best techniques to alleviate it from the environment. Fungi like Pleurotus ostreatus (Purnomo et al 2010), Gloeophyllum trabeum, Fomitopsis pinicola, Daedalea dickinsii (Purnomo et al 2011), Fomitopsis pinicola (Sariwati et al 2017) (Purnomo et al 2020), (Balaji et al 2014), Agaricus bisporus (García-Delgado et al 2015) and Scopulariopsis brevicaulis (Mao and Guan 2016) have been reported for alleviating the polyaromatic hydrocarbons from the environment. Fungi like Aspergillus sp., Penicillium sp., Fusarium sp., Rhizopus sp.…”
Section: Alleviation Of Environmental Pollutantsmentioning
confidence: 99%
“…Fomitopsis pinicola is a brown-rot fungus (BRF) that can produce metabolites to support the Fenton reaction (Contreras et al 2007;Purnomo and Mawaddah 2020;Purnomo et al 2010bPurnomo et al , 2011bPurnomo et al , 2020bRizqi et al 2021). Furthermore, several previous studies have reported that BRF can degrade toxic pollutants, namely (1,1,1-trichloro-2,2-bis (4-chlorophenyl) ethane, DDT; (Sariwati et al 2017;Sariwati and Purnomo 2018;Setyo et al 2018;Purnomo et al 2020b), polyvinyl alcohol (PVA; Tsujiyama and Okada 2013), as well as some dyes (Rizqi and Purnomo 2017;Purnomo et al 2019aPurnomo et al , 2020aPurnomo et al , 2020cPurnomo and Mawaddah 2020), both as a monoculture and a consortium with bacteria. This degradation ability correlates with the hydroxyl radical ( • OH) produced in the DDT degradation media by the BRF (Purnomo et al 2010b(Purnomo et al , 2020c.…”
Section: Introductionmentioning
confidence: 99%